Fitoteknologi Pengolahan Limbah Cair Depo Pemasaran Ikan (DPI) Kabupaten Sidoarjo Menggunakan Eceng Gondok (Eichhornia crassipes) dan Kangkung Air (Ipomoea aquatic) - Atik Widiyanti; Lily Oktavia; Ari Setiawan (2477 - 6165, 2020)
DPI Kabpaten Sidoarjo produces liquid waste from the fish washing process, which has the potential to pollute the environment. The results of the laboratory test of liquid waste produced by DPI Kabupaten Sidoarjo contains 764 mg/L BOD and 1.440 mg/L COD. DPI Kabupaten Sidoarjo uses phytoremediation methods with water hyacinth (Eichornia crassipes) and water spinach (Ipomoea aquatic). The parameters analysed were BOD5, COD, TSS, and TDS and biodegradability ratio. The reactor used was a 25 L batch reactor and the residence time used was 6 days. The results obtained by water hyacinth plants were able to reduce COD and BOD5 levels better than water spinach, namely 98.60% and 98.70%. Then the results of the TDS parameters of the water hyacinth reactor also got the lowest concentration of 368 ppm. For TSS parameters the best value was obtained from the water spinach reactor with a value of 400 mg/L. The pH parameters of the water hyacinth reactor and water spinach got a value between 6-7. The best biodegradability ratio was obtained from the water hyacinth plant reactor, which was 0.5-0.53.